Transcranial Motor Evoked Potentials during Spinal Deformity Corrections—Safety, Efficacy, Limitations, and the Role of a Checklist - Acharya, Shankar; Palukuri, Nagendra; Gupta, Pravin; Kohli, Manish (Frontiers in Surgery, 2017)
Introduction Intraoperative neuromonitoring (IONM) has become a standard of care in spinal deformity surgeries to minimize the incidence of new onset neurological deficit. Stagnara wake up test and ankle clonus test are the oldest techniques described for spinal cord monitoring, but they cannot be solely relied upon as a neuromonitoring modality. Somatosensory evoked potentials monitor only dorsal tracts and give high false positive and negative alerts. Transcranial motor evoked potentials (TcMEPs) monitor the more useful motor pathways. The purpose of our study was to report the safety, efficacy, limitations of TcMEPs in spine deformity surgeries, and the role of a checklist. Study design Retrospective review of all spinal deformity surgeries performed with TcMEPs from 2011 to 2015. Materials and methods All patients were subjected to IONM by TcMEPs during the spinal deformity surgery. Patients were included in the study only if complete operative reports and neuromonitoring data and postoperative neurological data were available for review. An alert was defined as 80% or more decrement in the motor evoked potential amplitude, or increase in threshold of 100 V or more from baseline. The systemic and surgical causes of IONM alerts and the postoperative neurological status were recorded. Results In total, 61 patients underwent surgery for spinal deformities with TcMEPs. The average age was 12.6 years (6–36 years) and male:female ratio was 1:1.3. Diagnoses included idiopathic scoliosis (n = 35), congenital scoliosis (n = 13), congenital kyphosis (n = 7), congenital kyphoscoliosis (n = 4), post-infectious kyphosis (n = 1), and post-traumatic kyphosis (n = 1). The average kyphosis was 72° (45°–101°) and the average scoliosis was 84° (62°–128°). There were in total 33 alerts in 22 patients (36%). The most common causes were hypotension (n = 7), drug induced (n = 5), deformity correction (n = 5), osteotomies (n = 3), tachycardia (n = 1), screw placement (n = 2), and electrodes disconnection (n = 1). Reversal of the inciting event cause resulted in complete reversal of the alert in 90% of the times. Three patients showed persistent alerts, out of whom one had a positive wake up test and woke up with neurodeficit, which recovered over few weeks, while the other patients showed persistent alerts but woke up without any deficit. Sensitivity and specificity of TcMEP in deformity correction surgery were 100 and 96.6%, respectively, in our study. Conclusion IONM alerts are frequent during spinal deformity surgery. In our study, more than 50% of the alerts were associated with anesthetic management. IONM with TcMEPs is a safe and effective monitoring technique and wake up test still remains a valuable tool in cases of a persistent alert.